Legal challenges in developing a digitalised electricity market in the EU: The case of Estonia - Javad Keypour (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2024)
Over the past decade, digitalisation has gained significant attention across various European Union (EU) policy areas, particularly in the energy sector. Along with this, digitalisation can contribute to higher energy security and sustainability of the EU energy systems especially by reducing fossil fuel dependency and distributing energy production through micro-renewable generation. However, digitalisation of electricity markets still deals with regulatory hurdles, especially within data management issues, and potential monopolies. Thus, this paper aims to address these challenges within Estonian market and focusing on prosumers' contributions to stabilising the digital electricity market through power generation or demand response. Applying document analysis of legal provisions and the multi-level perspective model of transition, the results indicate that while smart meters are pivotal in demand response and surplus electricity exchange, the current regulations create a de facto monopoly favouring Estonian suppliers, undermining prosumers' interests. Additionally, the concentration of data within a few aggregators can impede competition, while the lack of legal obligations for detailed data access hinders consumers' ability to engage in intra-day and balancing markets. The study highlights the need for legal provisions to facilitate data exchange and access for aggregators while addressing privacy concerns, thereby ensuring competition thrives. It also recommends establishing obligations for timely sharing of individual consumer consumption data and defining 'accounting points' to align with EU regulations. Additionally, clear definitions and provisions for data management, competition law compliance, and consumer rights are crucial. By implementing these recommendations, Estonia can enhance its role as a leader in digitalisation within the EU, promoting a more resilient and sustainable energy system.
Keywords: D42; K21; L94; O38; Q48; Q55; 330; Sustainability; Smart grids; Digitalisation; EU energy law; Electricity markets